Determination of Optimal Extrication Location of High Extraction Roadway of Large-Mining-Height Fully Mechanized Face - Xue-bo Zhang; Ming Yang (Advances in Civil Engineering)
Determining the optimal extrication location of the high extraction roadway can improve the gas extrication effect of highly gassy mine and solve the problem of gas concentration overrun at the upper corner, which is of great significance to safety and efficient mine production. According to the actual situation of mine, the gas gushing amount in the goaf, pressure difference at both ends of the working face, the 3D porosity, and permeability distribution of the caving zone and fissure zone were obtained by field measurement and numerical calculation. Through theoretical calculation, the proper extraction site of a high-position alley was determined. On this basis, the optimal extraction site of a high-position alley was determined by numerical analysis of the gas extraction effect at different sites. The results show that as the perpendicular distance between high-position alley and goaf floor increases, the gas extraction amount increases first and then decreases. The concentration of extraction gas gradually increases, and the increasing trend is gradually diminished. With the increase of the horizontal distance between the air return way and the high-position alley, the gas extraction amount and gas extraction concentration increase first and then decrease. The optimal extraction site of a high-position alley should be 39 m vertically away from the goaf floor and 30 m horizontally away from the air return way.